Validación de un dispositivo que establece y notifica la frecuencia de movimiento para prevenir úlceras por presión y caídas (2020)
This research was developed at the Fundación Cardioinfantil institution, in the line of research on sensors for the prevention of hospital events. To solve two specific problems, pressure ulcers due to long stays in bed, many of the patients in ICUs spend long periods of time in the same position, generating ulcers; as a second problem, institutional falls, where the patient for different reasons loses balance and falls, health personnel are not always informed in time to foresee these events. One of the growth factors of this problem is due to the current situation, which generated higher admissions of patients to the institution and therefore increased hospital events. Both problems can be fatal and the proposed device is expected to prevent these events. Course objective: To validate and determine the feasibility of a device that monitors movement changes, in order to be able to use it both for the prevention of falls and pressure ulcers. Methodology: The research practice was divided into two major stages which in turn will be divided into different phases. The first stage will be divided into two phases, a first phase where the project will be defined. In the second phase, three prototypes will be characterized and evaluated, determining the ideal device for the development of the research. Once the device is defined, the second stage begins, where the operation and feasibility of the device will be evaluated in four phases. In the first phase of stage two, the sensitivity of the device will be validated with a goniometer. In a second phase, the operation of the device will be validated in volunteers. In a third phase, the alarms for prevention of falls and the notifications of change of position for pressure ulcers will be validated with volunteers in a simulated environment. In a fourth phase, the feasibility of the device in patients in hospitalization and ICU will be analyzed. Results: Three prototypes were compared in order to select one and, according to the selected prototype, six identical devices were made, in the second stage four phases were carried out to determine the feasibility of the selected device, for this, sensitivity tests were carried out with goniometer, tests to determine the frequency of change of position in healthy adults during the night, in addition to the successful alarms in prevention of falls. For the feasibility phase with patients, only pressure ulcer prevention tests were performed.